FEMALE VIOLENCE AGAINST MEN IN WESTERN SOCIETIES: WOMEN AS HARASSERS IN TWO CONTEMPORARY LITERARY WORKS - Hassan, Adel El-Sayed; Alshara, Moayad Ahmad (European Scientific Journal, ESJ, 2015)
In western societies, the issue of female violence against men has received a great deal of attention recently. More specifically, the harassment of men at the hands of women has been widely addressed not only in the West but also in many countries across the world. Men have stereo-typically been looked upon as the ones who harass women. Unfortunately, many are still used to viewing men as the harassers rather than the harassed. However, this outlook has proved unfair. In the past two decades, there have been many cases of men being victims to female harassment in the real-life workplaces. This asserts the view that women, like men, are capable of harassing, that there is no exemption of gender when it comes to this, and that both men and women can become victims of harassment. This study investigates David Mamet’s Oleanna and Michael Crichton’s Disclosure to spot light on the female harassers and their male victims in both works. It explores the false sexual accusations made by the female characters against their male counterparts. It also depicts the female characters as harassers rather than harassed. The study concludes that harassment is no longer gender-specific, that women can and do harass like men, and that harassment, whatever form it takes, is a crime that must not be tolerated.